Measurement of Ribulose 1,5-Bisphosphate from Spinach Chloroplasts - Sicher, Richard C. (1979)
A technique has been developed for the rapid and simple measurement of ribulose 1,5-bisphosphate from isolated spinach chloroplasts. The endogenous ribulose bisphosphate was detected enzymically using (14)CO(2) and ribulose bisphosphate carboxylase/oxygenase released from the chloroplasts. Ribulose 5-phosphate kinase was inhibited with 0.4 to 0.6 millimolar 2,6-dichlorophenol-indophenol and 4 micromolar carbonyl cyanide m-chlorophenylhydrazone. Phosphoenolpyruvate carboxylase activity was low with washed chloroplasts and its labeled product, [(14)C]oxalacetate, was destroyed by heating with 1.0 n HCl at 90 C. The assay method was linear from 0.05 to 0.87 nanomoles ribulose bisphosphate per milliliter. The latter value was determined with chloroplast material having 44 micrograms of chlorophyll per milliliter. This technique was simple and direct, used less chloroplast material, yet provided results comparable to a previously described enzymic technique in which ribulose bisphosphate was determined after the precipitation of chloroplast proteins by perchloric acid.